STUDENTS’ WRITING DIFFICULTIES ON ONLINE LEARNING DURING COVID-19 PANDEMIC - Mora Yulina Simanihuruk; Dumaris E. Silalahi; Partohap Saut Raja Sihombing (Universitas Pahlawan Tuanku Tambusai, 2021)
This research aims to find out the students writing difficulties in recount text that faced by the students during online learning process. In performing data and data analysis qualitative research design was applied. It is based on basic interpretative analysis. It was used to describe topic related to the phenomenon happened in writing through online learning during pandemic covid-19. The object of this research was the students at tenth grade in SMA Swasta Teladan Pematangsiantar. In collecting data questionnaires were shared to 77 respondents. The research finding shows that the subjects have difficulties in writing recount text during online learning at situation of Covid-19 pandemic. The difficulties in four aspects of writing, they are sentence construction, organizing text, paragraphing aspect and text cohesion aspect. It is supported by the degree of percentage score of the questionnaires scores they are sentence construction aspect with Agree scale 55.2 %, organizing a text and paragraphing aspect with Agree scale 51.95 %, text cohesion aspect with Agree scale 51.95% and register/style aspect with Strongly Agree scale 47.5 %.